THE IMPACT OF RETURN ON ASSETS (ROA) AND RETURN ON EQUITY (ROE) ON STOCK PRICES: EVIDENCE FROM PT BANK RAKYAT INDONESIA (PERSERO) TBK (2014–2024) - Nobel Andrew Andries; Vicky Mundiahi; Fandy Yones Latuni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study investigates whether profitability explains stock price movements in a major Indonesian banking issuer, PT Bank Rakyat Indonesia (Persero) Tbk (BBRI), during 2014–2024. Motivated by mixed evidence on the value relevance of accounting performance in emerging markets, the research tests the effects of Return on Assets (ROA) and Return on Equity (ROE) on BBRI’s annual stock price. Using a quantitative design, the study analyzes annual secondary data (11 observations) compiled from audited financial statements and stock price records. Simple linear regression is used to estimate the partial effects of ROA and ROE, while multiple linear regression evaluates their joint explanatory power, with a 5% significance threshold. The partial results indicate that ROA is statistically insignificant (t = −1.341; p = 0.213; R² = 0.166) and ROE is also insignificant (t = −1.264; p = 0.238; R² = 0.151). In the multivariate model, both coefficients remain negative and insignificant, and the overall model is not significant (F = 0.838; p = 0.467), with modest explanatory power (R² = 0.173). These findings suggest that annual stock price variation in BBRI is driven primarily by factors beyond profitability, such as market sentiment and macroeconomic conditions. Practically, investors should avoid relying solely on ROA and ROE when valuing BBRI, while managers may need to complement profitability improvements with clearer market signaling. The study is limited by the small annual sample and potential omitted variables; future research should employ higher-frequency data and incorporate macro and bank-specific controls to improve inference and test non-linear effects.